Analisis Kebutuhan Layanan Konseling di SMPIT Al Mawaddah Warrahmah Kolaka - Awfiyah Balqis Zahirah; Sulkfili Ar (Universitas 45 Surabaya, 2025)
This study aims to analyze the counseling service needs at SMPIT Al Mawaddah Warrahmah Kolaka as a foundation for developing guidance and counseling programs that are relevant to students’ characteristics. The research employed a qualitative descriptive approach, involving counseling teachers, homeroom teachers, and students as participants. Data were collected through in-depth interviews, observations, and counseling needs questionnaires. The results revealed that students have high counseling needs, particularly in the academic and social aspects, such as difficulties in managing study time, low learning motivation, and social relationship issues within the school environment. The existing counseling services tend to be incidental and reactive, lacking a systematic needs-based assessment. Consequently, the effectiveness of the counseling program in supporting students’ holistic development remains limited. The study recommends the implementation of need-based counseling programs, the enhancement of counselor competencies, and stronger collaboration among subject teachers and homeroom teachers. Therefore, counseling services can function not only as a problem-solving mechanism but also as a means of fostering students’ character and potential development.